High‐boron and High‐alumina Middle Byzantine (10th–12th Century ce) Glass Bracelets: A Western Anatolian Glass Industry. (27th June 2017) - Swan, C. M.; Rehren, Th.; Dussubieux, L.; Eger, A. A.
Abstract : The trace element boron is present in most ancient glasses as an impurity, and high boron (≥ 300 ppm) marks raw material sources that are geologically specific and relatively uncommon. Recent analyses of Byzantine glass with high boron contents suggest that glass‐making was not limited to the traditional regions of the Levant and Egypt, and a production origin in or near western Anatolia is proposed. Glass bracelets from Ḥiṣn al‐Tīnāt in southern Turkey give fresh evidence for the production and circulation of high‐boron glasses that closely correlates with object typology. The patterning of findspots suggests that high‐boron glass was closely connected to the Byzantine world.